Finite Element Analysis on the Effect of Hollow Section on the Strength of Foamed Concrete Beam - Rokiah, Othman; Khairunisa, Muthusamy; Putra Jaya, Ramadhansyah; Duraisamy, Youventharan; M. A., Sulaiman; Nadiatul Adilah, Ahmad Abdul Ghani; Chong, B. W. (IOP Publishing, 2020)
The environmental impact of cement production has prompted innovative measures to reduce the usage of cement in accordance with the principle of sustainable construction. At the same time, the palm oil industry generates about 2 million tons of spent bleaching earth (SBE) are generated annually with most of it ends up in the landfill, causing environmental degradation. This research focuses on the effect of hollow section on the strength of foamed concrete beam by using processed spent bleaching earth (PSBE) as partial cement replacement. Hollow section of two shapes were implemented at three different locations along the beam specimen. The foamed concrete beams with 30% cement replaced with PSBE were subjected to tensile test at 28 days to observe the effect of hollow section on the maximum load and tensile strength. The deflection of the specimen was compared with theoretical value and the mode of failure was studied. Hollow section of circular and square shape was studied while the locations were on neutral axis, above neutral axis, and below neutral axis. Verification of experiment was conducted using Finite Element Analysis (FEA) software, ANSYS. Test result shows that beams with circular hollow section has higher strength than those with circular hollow sections. The best position of hollow was above the neutral axis as to not impact the weak tensile strength of foamed concrete. FEA analysis shows great accuracy in predicting the performance of the specimens.